(untitled) (Journal on studies and research of academic knowledge, 2022)
The objective of the study was the artisanal production of Trichoderma spp. for its potential application in sustainable biological control in urban and sub-urban gardens in the district of Encarnación and Capitán Miranda, Itapúa during the year 2021. The descriptive study developed a quantitative approach with a non-experimental. Local people garden plots were evaluated considering characteristics of the environment and temporary spaces for the execution of the actions. The sampling of fungi was considered for the isolation and PDA culture media were prepared for sowing. Trichoderma has three types of propagules: hyphae, chlamydospores and conidia; the last two are the most stable, which is why conidia germination was evaluated to determine viability, obtaining satisfactory values. The substrate is suitable to generate suspensions of conidia in acceptable concentrations to be used in field applications. The content of organic fertilizers in soil favors the development of the fungus, a condition that was observed in the gardens of the district of Capitán Miranda. The versatility of growth and the benefits that the strains of Trichoderma spp. have made promising its use to make phytopathogenic biocontrol products.